(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2024)
This study sought to identify drivers that explain the purchase and repurchase intention of Brazilian consumers of fresh food products via delivery during the Covid-19 pandemic. This investigation is qualitative, developed in two phases: an exploratory phase through in-depth interviews and Content Analysis to explore the content corpus. It turned out that the 7 P’s of Services Marketing are considered by interviewees as decisive elements for the purchase of fresh food products via delivery, as well as other new constructs identified. The second phase was explanatory, developed from a questionnaire and Coincidence Analysis (cna). The results reiterate the importance of combinations between the constructs of the 7 P’s of services marketing, the Theory of Planned Behavior, User Experience, Satisfaction, Trust and Security, Practicality and Convenience, and Perception of risk in relation to health and Covid- 19 in the studied context.